Observations on the Seasonal Abundance of Sorghum Midge - Anthony Zukoff (Kansas Agricultural Experiment Station Research Reports, 2023)
Sorghum midge,Stenodiplosis sorghicola(Coquillett), is a major pest of sorghum production worldwide. Midge larvae develop within the sorghum spikelet protected from predation and chemical control. Feeding by larvae prevents grain development resulting in varying degrees of blank heads. Historically, sorghum midge has been considered a minor pest in Kansas. In recent years, significant midge infestations have been documented in several locations of the southwest and southeast portions of the state. Some basic information on sorghum midge seasonality in Kansas will help to refine some management recommendations if this pest becomes more prevalent. Sorghum midges were recovered from samples taken every week of this study. Samples collected during the first week of August contained the lowest number of midges while the highest number of midges recovered came from samples collected on August 15. The percent of samples infested was lowest on August 8 at 40%. Infestation across the remainder of the study ranged from 60 to 100%.
Keywords: sorghum midge; Stenodiplosis sorghicola; Diptera; Cecidomyiidae; sorghum